Changes of ghrelin and brain natriuretic peptide levels in systemic vascular resistance after cardiopulmonary bypass - Rahman, A.; Aydin, S.; Bayar, M. K.; Sahin, I. (Springer, 2008)
The application of cardiopulmonary bypass (CPB) using a heart-lung machine in open heart surgery is associated with numerous pathophysiological changes in the vascular system and the neurohormonal environment. In this study our purpose was to investigate whether the hormones brain natriuretic peptide (BNP) and ghrelin arc involved in changes in the systemic vascular resistance index (SVRI) after CPB, using data from 20 patients who had undergone coronary artery bypass grafting accompanied by CPB. Hemodynamic measurements were obtained using a thermodilution catheter and included cardiac index and systemic vascular resistance index. Blood samples were taken before CPB, after CPB, and at 0 and 24 h postoperatively. The blood levels of total and acylated ghrelin were quantified by radioimmunoassay. Blood levels of BNP were measured by a fluorescence immunoassay kit. The SVRI was significantly higher at the end of CPB and at 0 h postoperatively than before CPB (end of CPB: 4282 +/- 1035 dyne . s . cm(-5). m(-2), 0 h postoperatively: 3239 635 dyne . s . cm(-5). m(-2) vs. before CPB: 2289 +/- 330 dyne . s . cm(-5). m(-2), p < 0.05). Total and acylated ghrelin levels decreased until 0 h postoperatively but the change was not statistically significant. However, at 24 h after surgery, they showed a statistically significant increase over the initial ghrelin values (total before CPB: 1413.71 +/- 287.93 pg/ml vs. 24 h postoperatively: 1736.85 +/- 236.89 pg/ml; acylated ghrelin before CPB: 55.85 +/- 25.53 pg/ml vs. 24 h postoperatively: 106.28 +/- 30.86 pg/ml; p < 0.05 for both). BNP values were markedly lower after than before CPB (before CPB: 69.07 +/- 48 pg/ml vs. after CPB: 21.96 +/- 13 pg/ml, p < 0.05) and reached a maximum value 24 h postoperatively (before CPB: 56.3 +/- 42 vs. after CPB: 454.7 +/- 229 pg/ml, p < 0.05).
Keywords: Ghrelin; Brain natriuretic peptide; Systemic vascular resistance; Cardiopulmonary bypass